The Analysis of Female's 100-Meter Sprinters in Tokyo Olympic Games 2022 (Universitas Negeri Semarang, 2022)
This research aimed to identify the performance of the female's 100-meter final at the Tokyo Olympic Games 2022. This study was conducted in a quantitative approach and descriptive methods. There were 8 female sprinters aged 28 ± 3.70 years old who were competing in the 100-meter final at Tokyo Olympic Games 2022. The data were analyzed from a YouTube video of the Olympic channel The kinematic analysis by using Kinovea computer software was conducted to measure the variables in this study. The variables were time per 10 meters (s), velocity per 10-meter (m/s), step per 10-meter (step), and time per step (s). As the result, the champion achieved a stable time in the second to seventh 10-meter (0.77 – 0.84 s) as well as the fastest average velocity in 100 meters (9.43 m/s). She runs more than 12 m/s in 60 meters distance. It is more consistent than the runner-up (athlete in line 5) who runs more than 12 m/s in 5 10-meter distances. She also achieved a total of 50 steps with an average of 5 steps in every 10-meter distance. It is two steps more than the tallest athlete (173 cm) who achieved 48 steps in 100 meters. The mean time per step of the champion is 0.21 ± 0.03 s/step. In conclusion, the consistency of step frequency and velocity determined the positive result.